1988
DOI: 10.1159/000215781
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Coagulation System in Tumor-Cell-Induced Platelet Aggregation and Metastasis

Abstract: The ability of tumor cells to initiate coagulation and subsequent platelet aggregation is believed to facilitate the metastatic process. The mechanism by which tumor cells initiate thrombotic alterations is unclear. We have purified a plasma membrane protein platelet aggregating activity/procoagulant activity (PAA/PCA) from several rodent tumors which initiates the coagulation of homologous plasma and aggregation of homologous platelets by a mechanism independent of factor VII. This protein does not possess an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…Both molecules are ultimately responsible for the activation of factor X, which in turn leads to the generation of active thrombin from plasma prothrombin (15). All these observations would suggest that thrombin generation caused by tumor procoagulant activities might be responsible for in vivo platelet activation (16) and the release of biologically active substances, as demonstrated recently for vascular endothelial growth factor (12).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Both molecules are ultimately responsible for the activation of factor X, which in turn leads to the generation of active thrombin from plasma prothrombin (15). All these observations would suggest that thrombin generation caused by tumor procoagulant activities might be responsible for in vivo platelet activation (16) and the release of biologically active substances, as demonstrated recently for vascular endothelial growth factor (12).…”
Section: Introductionmentioning
confidence: 71%
“…Preclinical and clinical studies suggested that activation of the hemostatic system may play an important role in tumor growth and metastasis. Indeed, it is well known that many human tumors possess a procoagulant activity that can be responsible for the generation of active thrombin from plasma prothrombin (15), leading to in vivo platelet activation (16) and release of various factors, including growth factors and cytokines, most of which may have important biological functions in the development and progression of human tumors (12,23).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells are unique because they have constitutively active tissue factor on the surface. 37,38) The tissue factor could induce thrombin generation, which in turn could stimulate tumor cell growth, adhesion, and invasion. In the presence of hirudin, thrombin activity could be inhibited hence resulting in a decreased trend in ability of tumor cell adhesion, growth, invasion, and metastasis.…”
Section: Effect On Tumor Cell Proliferation In Vivomentioning
confidence: 99%
“…In an experimental metastasis model, tumor cell-associated TF stimulates the formation of tumor cell/platelet/fibrin complexes, which greatly enhance tumor cell seeding in the lungs. 4,6,7 The major physiologic inhibitor of the TF/fVIIa complex is the tissue factor pathway inhibitor (TFPI). 1 TFPI is a multidomain protein consisting of 3 independently folded kunitz proteinase inhibitor (KPI) domains, and a highly basic carboxy-terminal tail.…”
Section: Introductionmentioning
confidence: 99%